An unusual presentation of low ulnar nerve palsy: a case report - Kaur, Eknoor; Saini, Narender (International Journal of Research in Orthopaedics, 2021)
Ulnar nerve compression at the Guyon’s canal is an uncommon cause of ulnar nerve neuropathy. Among various reasons like trauma, non-union of hook of hamate, anomalous muscle anatomy, thrombosis of the ulnar artery or pseudoaneurysm, ganglion is a common lesion which can compress the ulnar nerve at this site. With proper history taking and physical examination consisting of assessing motor functions and sensation of the hand, a clinician can localize the site of the lesion. Ultrasound is cheap and non-invasive technique which helps to localize the site of lesion and can suggest the nature of the lesion. Surgical decompression of the canal and careful removal of the lesion can help ameliorate the symptoms. In our study the patient presented with sudden onset weakness of the right hand and symptoms progressing within one and half month. With proper muscle charting, sensory examination and with the help of sonography, the main culprit was localized to Guyon’s canal. Excision of the lesion helped in recovery of hand function within 5 months.